Contribution to the knowledge of the Philippines species of the tribe Odacanthini Laporte, 1834 (Coleoptera: Carabidae) - Anichtchenko, Alexander; Sciaky, Riccardo (Zootaxa, 2024)
In this work we describe a new species from the Philippines (Luzon Island). Archicolliuris albolineata sp. n. is allied to A. tenuis from Borneo and Palawan, and can be distinguished by having the much longer elytral white stripe and the wider pronotum. Three species, Mimocolliuris (Paramimocolliuris) insulana Habu, 1979; Ophionea (s. str.) celebensis Baehr, 1996 and Ophionea (Procasnoidea) foersteri Bouchard, 1903, are recorded for the first time in the Philippines. Some new nomenclatural acts are here proposed: Colliuris philippinensis Donabauer, 1996 = Mimocolliuris philippinensis (Donabauer, 1996) n. comb.; Ophionea (Setophionea) ishiii hoashii Habu, 1961 = Ophionea (Setophionea) ishiii ishiii Habu, 1961 n. syn.; Casnoidea (s. str.) leytensis Baehr, 1996 = Ophionea (Setophionea) ishiii ishiii Habu, 1961 n. syn.; Ophionea (s. str.) bhamoensis Bates, 1892 = Ophionea (s. str.) bakeri Dupuis, 1913 n. syn.; Ophionea (s. str.) bhamoensis Bates, 1892 = Ophionea bhamoensis taiwanensis Terada & Wu, 2014 n. syn. Numerous taxonomic comments are also provided. Illustrations of the habitus of all the species are given, and new distributional data are provided.